Experimental investigation of thermal storage in U-tube heat exchanger - Cakmak, Gulsah (Pergamon-Elsevier Science Ltd, 2013)
In the industry there are several measures and applications that can be performed in order to enhance energy efficiency, one of which is the evaluation of disposed energy. One of the most widely used processes for recycling the disposed energy is the employment of the heat exchanger systems which ensure heat exchange between two or more fluids at different temperatures. In this paper a U-tube heat exchanger has been designed and waste heat has been stored by using phase change material in the system. Calcium chloride hexahydrate with 29 degrees C melting temperature was used as phase change material and water was used as heat transfer fluid. It has been determined that 588 kJ and 417 kJ heat energy can be stored at two different water inlet temperatures of 65 degrees C and 45 degrees C, respectively. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: U-tube heat exchanger; Thermal energy storage; Salt hydrate